Penggunaan Alat Cetak untuk Produksi Jaja Saga - Dewa Ngakan Ketut Putra Negara; I M Gatot Karohika; I D M Krishna Muku (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2016)
Every place in Bali has a food specific characteristic. Gianyar region is known with its jaja klepon and Klungkung is famous with serombotan. In Melinggih Kelod Village, District of Payangan is developing a type of food, called jaja saga. Micro industries of producing this food are made by some households in this village. The steps of making jaja saga follow; preparing of row materials (coconut, rice powder, sugar, salt and water), mixing of the row materials, leveling of row materials on the taplon and roasting. After 10 minutes jaja saga has cooked. The final process is packaging. The leveling of row materials on the taplon process is the stage that needs the long enough time; it is about 5 to 8 minutes. To overcome the problem, it is made a molding jaja saga device. The principle work of the device is by pressuring a circle-pressure device with 17.90 cm in diameter trough a mold hole with 18 cm in diameter. Pressuring mechanism is undertaken by chain, sprocket and thread of the screw transmission with handle mover. The results of device test show that device work mechanism has successfully worked but improving regarding with the type of row materials used is needed so better results will be obtained.